The Effect of Exposure to Scientific Ads on TikTok on Buying Interest (Quantitative Study on Indonesian Scientific Followers) - Jannah, Raihanil; Purworini, Dian (Universitas Muhammadiyah Surakarta, 2023)
Advertising has become one of the special forms of communication to solve marketing tasks. Advertising is more than just sharing information with the public. Many platforms can be used as advertising platforms, including TikTok. TikTok was originally a short video-sharing platform, specifically lip sync and dance videos, but over time, TikTok developed into a full-featured video service with various types of content. Scientific Indonesia is one of the brands that uses TikTok as its advertising platform. This research uses the S-O-R Theory. This study aims to determine the effect of exposure to Skintific ads on TikTok on buying interest. This study used a quantitative descriptive method. The population of this study was 535,200 followers of the scientific Indonesian TikTok account. The sample in this study amounted to 215 people using the Purposive Sampling method. Data collection techniques using questionnaires in the form of Google Forms. Test the data using IBM SPSS Statistics 23. the results of this study show that exposure to scientific on TikTok has a positive impact on being interested what the collection. This study achieved results showing that exposure to scientific ads on TikTok (X) has a positive effect on Buying Interest (Y). This research is useful in providing information to brands to improve marketing communication, especially advertising further because the result of this research is an advertisement that is very influential on product buying interest. One of them is scientific, where the correlation value (R) is 0.511, and the value of R square X to Y is 0.261. This means that the contribution of exposure to Indonesian scientific advertisements on the TikTok application to buying interest is 26.1%. In comparison, the remaining 74.9% is influenced by other variables that are not studied. In addition, the value of sig. 0.000 < 0.05, where the conclusion H0 is rejected and Ha is accepted.